2015
DOI: 10.1089/vbz.2015.1786
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasite Infestations and Canine Infection by Rickettsiae and Ehrlichiae in a Semi-Arid Region of Northeastern Brazil

Abstract: This study investigated the prevalence of Rickettsia spp. and Ehrlichia canis infection in dogs and their ectoparasites from rural and urban areas of two municipalities, Petrolina and Juazeiro, within a semiarid region (Caatinga biome) of northeastern Brazil, by immunofluorescence assay (IFA) and polymerase chain reaction (PCR). Overall, 12.1% (61/504) and 23.0% (116/504) of canine plasma samples had antibodies reactive to Rickettsia spp. and E. canis. E. canis DNA was detected by PCR in 8.3% (42/504) of canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
6
0
2
Order By: Relevance
“…According to Piranda et al (2008) the presence of seropositive animals indicates the circulation of Rickettsia of the SFG in an area at least 6-18 months earlier. As common hosts of tick-vectors for BSF, dogs are an important marker for disease in surveillance studies, and the occurrence of serologically positive dogs in a geographical area indicates the threat of human infection (ARAES-SANTOS et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to Piranda et al (2008) the presence of seropositive animals indicates the circulation of Rickettsia of the SFG in an area at least 6-18 months earlier. As common hosts of tick-vectors for BSF, dogs are an important marker for disease in surveillance studies, and the occurrence of serologically positive dogs in a geographical area indicates the threat of human infection (ARAES-SANTOS et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A similar seropositivity rate was previously observed by Costa et al (2015), who found antibodies to this agent in 14.6% of the dogs from rural and urban areas of the state of Maranhão, Brazil. Higher seropositivity rates among dogs have been reported in studies conducted in other states in northeastern Brazil: Paraíba 72.5%, 69.4%, 23% and 34% (ARAES-SANTOS et al, 2015;AZEVEDO et al, 2011;ROTONDANO et al, 2015;TANIKAWA et al, 2013); and Bahia 23.0%, 36% and 35.6% (ARAES-SANTOS et al, 2015;CARLOS et al, 2007;SOUZA et al, 2010).…”
Section: Discussionmentioning
confidence: 64%
“…Other highest values of seropositivity in dogs were reported in Northeastern Brazil: Paraiba 72. 5%, 69.4%, 23% and 34% (AZEVEDO et al, 2011;TANIKAWA et al, 2013;ARAES-SANTOS et al, 2015;ROTONDANO et al, 2015), and Bahia 23.0%, 36% and 35.6% (CARLOS et al, 2007;ARAES-SANTOS et al, 2015). and inclusions, suggestive of Ehrlichia spp., were detected in 6.5% (13/198) of dogs with clinical signs suggestive of canine monocytic ehrlichiosis (MEDEIROS; LIMA, 2004).…”
Section: Discussionmentioning
confidence: 99%